Lateral cephalometric radiograph analysis on obstructive sleep apnea patients - Resky Mustafa; Menik Priaminiarti; Hanna Huzaima Bachtiar Iskandar; Bramma Kiswanjaya (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2022)
Objectives: This review article is aimed to investigate changes in anatomical factors in Obstructive Sleep Apnea (OSA) patients through means of a cephalometric radiograph, which covers relation and size. Review: This literature review used online databases (PubMed and Scopus) discussing obstructive sleep apnea (OSA) in adults aged 18-80 years, using cephalometric analysis, and several keywords such as “obstructive sleep apnea and cephalometry” were employed to do the literature search. The search was limited to full-text articles written in English and published during the 2011-2021 period. Articles were selected by complying with literature review guidelines. Conclusion: Dentists can detect OSA early through lateral radiograph, which is originally an early screening tool, by paying attention to patients’ position during exposure, irradiation condition (kV, mA and Sec) and patient position in OSA diagnosis in regards to hard and soft tissue being evaluated. The specific craniofacial morphological variable could be a reliable parameter in determining the existence of OSA.